Challenges to Protecting the Right to Health under the Climate Change Regime - Chuan-Feng Wu (Harvard FXB Center for Health and Human Rights, 2020)
Researchers and global policy makers are increasingly documenting negative health impacts from climate change, raising concerns for realizing the right to health. Importantly, courts have held that anthropogenic activities affecting climate may threaten a population's standard of health and compromise its inviolable right to health. However, legal hurdles-such as the fragmentation of climate change and human rights laws and the difficulties in proving causal links-hamper efforts to litigate right to health claims in the context of climate change. To address these challenges, this article assesses the detrimental effects of climate change from an international human rights perspective and analyzes climate change litigation to explore potential avenues to press for the right to health in the face of climate change.